BIMBINGAN TERPADU OLIMPIADE SAINS NASIONAL BIDANG MATEMATIKA SISWA SMP NEGERI 2 MERAUKE - Rian Ade Pratama; Dessy Rizki Suryani; Andi Saparuddin Nur (Bahasa Indonesia, 2020)
Abstract This article discusses a new concept of complete guidance of the national science olympiad in the field of mathematics. This guidance is carried out periodically with the aim of providing new experiences for students in preparation for the 2020 national science olympiad. Assistance for national science olympiad guidance is carried out in three main steps. First, the results of observations made to discuss students and schools in the implementation of national science olympiad guidance at school. In this observation, an explanation was obtained about the school where the community service had not contributed to the national science olympiad five years ago. Second is the socialization stage. At this stage of socialization is the initial part made. The socialization consisted of the socialization of the national science olympiad guidebook and online technical guidance socialization with Edmodo application platform. Socialization is carried out in accordance with predetermined planning. The third is the evaluation stage. The evaluation stage is the final stage of the national science olympiad guidance. This final phase is fully supported in the implementation of integrated guidance. Evaluation of the National Science Olympiad book and evaluation of the use of Edmodo application in online guidance. The evaluation book consists of revised material that is suitable for junior high school level learning material and high-level evaluation material. Online tutoring evaluation is done by activating student guidance in online tutoring. Abstrak Artikel ini membahas tentang suatu konsep baru bimbingan terpadu olimpiade sains nasional dalam bidang matematika. Bimbingan ini dilakukan secara berkala dengan tujuan untuk memberikan pengalaman baru untuk siswa dalam persiapan olimiade sains nasional tahun 2020. Pelaksanaan bimbingan terpadu olimpiade sains nasional dilakukan dalam tiga tahapan utama. Pertama, adalah tahapan observasi yang dilakukan untuk mengetahui permasalahan siswa dan sekolah dalam pelaksanaan bimbingan olimpiade sains nasional disekolah. Pada observasi ini diperoleh penjelasan bahwa sekolah yang menjadi tempat pengabdian belum berkontribusi dalam olimpiade sains nasional pada lima tahun belakangan. Kedua adalah tahapan sosialisasi. Pada tahapan sosialisasi ini merupakan pengenalan awal prosedur bimbingan terpadu. Sosialisasi terdiri dari sosialisasi buku panduan olimpiade sains nasional dan sosialisasi teknis bimbingan online dengan platform aplikasi Edmodo. Sosialisasi dilakukan secara bertahap sesuai dengan perencanaan yang telah ditentukan. Ketiga adalah tahapan evaluasi. Tahapan evaluasi merupakan tahapan akhir dari bimbingan terpadu olimpiade sains nasional. Tahapan akhir ini mengevaluasi secara keseluruhan dalam pelaksanan bimbingan terpadu. Evaluasi buku olimpiade sains nasional dan evluasi penggunaan aplikasi Edmodo dalam bimbingan online. Evaluasi buku terdiri dari pemisahan materi yang sesuai dengan materi pembelajaran tingkat sekolah menengah pertama dan mengevaluasi seluruh kesalahan dalam penulisan-penulisan. Evaluasi bimbingan online dilakukan dengan mengaktifkan secara terjadwal aktifitas siswa dalam bimbingan online.